2006
DOI: 10.2320/matertrans.47.1155
|View full text |Cite
|
Sign up to set email alerts
|

FE-SEM Study of Microbially Formed Jarosites by <I>Acidithiobacillus ferrooxidans</I>

Abstract: Morphological characterization of jarosite groups formed from Fe(III) biologically oxidized with different numbers of Acidithiobacillus ferrooxidans was conducted using FE-SEM. The higher population of A. ferrooxidans resulted in more distinct jarosite mineral shape, and stronger Raman intensities for potassium jarosite, ammoniojarosite and argentojarosite. The morphology of the jarosites might be dependent on iron-oxidizing activity of A. ferrooxidans.The technique was applied to identify jarosite compounds f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The occurrence of argentojarosite (AgFe 3 (SO 4 ) 2 (OH) 6 ) is rare relative to other jarosite-group endmembers; however, it accounts for a substantial fraction of Ag within gossan and is thought to reflect the early phases of gossanization [23,24]. Under acidic weathering conditions, such as those occurring within and around open pit mine sites, dissolved Fe 3+ , H + and SO 4 2− can form jarosite-group minerals that could act as a "sink" for Ag + [25][26][27][28][29][30]. …”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of argentojarosite (AgFe 3 (SO 4 ) 2 (OH) 6 ) is rare relative to other jarosite-group endmembers; however, it accounts for a substantial fraction of Ag within gossan and is thought to reflect the early phases of gossanization [23,24]. Under acidic weathering conditions, such as those occurring within and around open pit mine sites, dissolved Fe 3+ , H + and SO 4 2− can form jarosite-group minerals that could act as a "sink" for Ag + [25][26][27][28][29][30]. …”
Section: Introductionmentioning
confidence: 99%
“…4 shows a FTIR spectrum with different vibration modes. It indicated that: the absorption peak at 3353 cm −1 was ascribed to the O\H stretching; the ν4, ν3, ν2 and ν1 vibrations of sulfate were represented in the wavenumbers of 626 cm and 1006 cm −1 , respectively (Henao and Godoy, 2010); the vibration peaks of FeO 6 octahedron were observed in the wavenumbers of 511 cm −1 and 473 cm −1 (Sasaki et al, 2006). Consequently, the above results prove the precipitates bio-mediated to be jarosites.…”
Section: Characteristics Of Natrojarositementioning
confidence: 57%
“…It is crucial to minimize jarosite formation in order to increase efficiency (Chung et al, 2005;Wang et al, 2007). So the formation of jarosite during the oxidation of ferrous iron by A. ferrooxidans was studied (Sasaki et al, 2006;Liao et al, 2009;Daoud and Karamanev, 2006). On the other side jarosite is an excellent mineral pigment in mural paintings, tiles and ceramic products.…”
Section: Introductionmentioning
confidence: 99%
“…Acidophilic, iron-oxidizing bacteria produce increased H + concentrations as well as schwertmannite and hydronium jarosite ((H 3 O)Fe 3 (SO 4 ) 2 (OH) 6 ) as by-products of their active metabolism. These IOM precipitates occur as pseudoacicular and euhedral crystal morphologies, respectively [11,17,18,29,30]. The average pH of the bacterial enrichments was determined, and IOM precipitates were collected, air dried for 24 h, and weighed to obtain an average mass.…”
Section: Iron-oxidizing Bacterial Enrichmentmentioning
confidence: 99%
“…From a biogeochemical perspective, acidophilic, iron-oxidizing bacteria, e.g., Acidithiobacillus ferrooxidans and Leptospirillum ferriphilum, are known to colonize and accelerate the dissolution of metal sulfides. In doing so, they form secondary iron oxyhydroxide mineral (IOM) precipitates, such as schwertmannite, which comprises TIFs [1][2][3][4][5][6][7][8][9][10][11][12]. In addition to chemolithotrophic bacteria, iron oxidation has also been attributed to phototrophic microbes, such as cyanobacteria and algae, which produce oxygen as by-products [2].…”
Section: Introductionmentioning
confidence: 99%